SARANA UPACARA AGAMA HINDU SEBAGAI ELEMEN DAYA TARIK PARIWISATA - Reni Ariasri, Nyoman (JURNAL KEPARIWISATAAN, 2010)
Many countries develop tourism as an important sector because of the huge market demand and it is considered as an environmentally friendly industry. Howeve1; the impact of tourism development on local culture cannot be avoided. Bali as one of the international tourism destinations also experiences same problems that the tourism development has positive and negative impacts 011 the physical and ecological environment and culture of Bali. In 1990s the debate on the relationship between tourism and culture in Bali dominated the public discourse. The commodification, culture degradation, lose of authenticity, and organization, have been questioned again recently, either in term of theoretical conception, or empirically. One of the focus of the discourse is that the use of items in Hindu religious ceremony as tourist attraction. Therefore, this article is aimed at discussing the items used in Hindu religious ceremony as an element of tourist atraction and it is expected that the impact on Balinese culture can be constructed theoretically and empirically.